Preparation and Characterization of Anadara Granosa Shells and CaCO3 as Heterogeneous Catalyst for Biodiesel Production - Hadiyanto Hadiyanto; Sri Puji Lestari; Widayat Widayat (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
Nowadays, the use of homogenous catalyst has been gradually reduced for its operational reason. The homogenous catalyst leads in difficulty of separation after the process completed and the life cycle is shorter. Therefore, most of researches are introducing heterogenous catalyst for its substitution. This research was aimed to evaluate the use of shell of Anadara granosa and CaCO3 as source of CaO based catalyst through impregnation method. The preparation of the catalyst was started by decomposition of shells and CaCO3 at temperature of 800 oC for 3 hours, followed by impregnation at 70 oC for 4 hours and then calcined at 800 oC for 2 hours. The CaCO3 based catalyst gained high yield of biodiesel (94%) as compared to Anadara granoasa based catalyst (92%). The reusability study showed that these catalysts could be used until three times recycle with 40-60% yield of biodiesel. The CaO contents of catalyst decreased up to 90% after three times recycles.